Phosphorus forms and adsorption properties of paddy field soils and potential risk to Indawgyi Lake, Myanmar - Mohammad Rafiul Hashar; Shamima Nasrin (Discover Environment, 2024)
Abstract The largest freshwater and oligotrophic lake in northern Myanmar, called Indawgyi Lake, is at potential risk of eutrophication due to the phosphorus (P) export from nearby paddy fields. In this study, the P status of the soil of paddy fields and its potential mobility to the lake water to cause eutrophication have been evaluated. The Indawgyi Lake is the third largest lake in Asia and became a UNESCO biosphere reserve in June 2017 for its outstanding contribution to providing habitat for threatened birds and aquatic species. Although many other sources, e.g. high tourist interest, loss of natural forest areas, the gathering of pilgrims and lack of proper wastewater treatment plants are contributing to the P nutrients input to the lake, the increase of paddy fields around the lake area and use of synthetic fertiliser which exports to the lake is considered to the primary source of P export to the lake. In this study, the soil P was examined with different P extracted methods and P export to the lake was calculated. The extracted P differed in order and magnitude with different methods, and the order was increased in accordance with CaCl2 < DL-P < Olsen-P < BD-P < HCL-P < TP and for iron, it was HCl-Fe < TFe. All extracted Olsen-P was below 10 mg kg−1, which is below the critical level (30–172 mg kg−1) for P loss. On the other hand, the soil has a high P sorption capacity, and the maximum sorption capacity among the soil samples that were done with the Langmuir equation is 0.790 mg g−1. Our findings suggested that paddy fields are not contributing to the eutrophication of the lake at present. However, comparing the historical map around the lake area from 1944 to 2017, it has been found that the area of paddy fields around the lake has increased almost three-fold from 1944 to 2017. As a result of increasing paddy fields and synthetic fertiliser use, we can say that P export from paddy fields can cause severe eutrophication to the lake in the near future.